INFLASI, PENGANGGURAN DAN PERTUMBUHAN EKONOMI DI NEGARA-NEGARA ISLAM - Muchdie M. Syarun (Universitas Muhammadiyah Prof Dr Hamka, 2016)
This paper discuss on inflation, unemployment and economic growth in Islamic State Nations. There are two types of Islamic state nations in this study, namely Islamic states that have adopted Islam as the ideological foundation and constitution (6 countries) and the other one is that Muslim- majority nation-states that have endorsed Islam as their state religion (14 countries). The Philips curve does exist in the countries as indicated by negative correlation between inflation rate and the rate of unemployment which was statistically significant, although the coefficent of determination was very small. Multiple regression analysis which inflation and unemployment were independent variables and economic growth was dependent variable showed that there were not significant simultant negative influences of the rate of inflation and the rate of unemployment toward economic growth. But, partially both inflation and unemployment have significant negative impact on economic growth in Islamic countries.